2012
DOI: 10.1073/pnas.1114052109
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of functional, amphipathic amyloid monolayers by the fungal hydrophobin EAS

Abstract: The hydrophobin EAS from the fungus Neurospora crassa forms functional amyloid fibrils called rodlets that facilitate spore formation and dispersal. Self-assembly of EAS into fibrillar rodlets occurs spontaneously at hydrophobic:hydrophilic interfaces and the rodlets further associate laterally to form amphipathic monolayers. We have used site-directed mutagenesis and peptide experiments to identify the region of EAS that drives intermolecular association and formation of the cross-β rodlet structure. Transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
115
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 54 publications
(73 reference statements)
5
115
0
7
Order By: Relevance
“…[21][22][23][24] Since amyloids are generally derived from natural proteins, they have a low immunogenic and inflammatory potential, due to their intrinsic biocompatibility. 2,8,[25][26][27][28] Earlier studies have demonstrated that highly ordered amyloid cross-beta structures are associated protein-specific amyloid core sequences of four to seven amino acids. [29][30][31][32] The core sequences are able to self-assemble into structurally highly similar fibrils that resemble the fibrils derived from the entire protein.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Since amyloids are generally derived from natural proteins, they have a low immunogenic and inflammatory potential, due to their intrinsic biocompatibility. 2,8,[25][26][27][28] Earlier studies have demonstrated that highly ordered amyloid cross-beta structures are associated protein-specific amyloid core sequences of four to seven amino acids. [29][30][31][32] The core sequences are able to self-assemble into structurally highly similar fibrils that resemble the fibrils derived from the entire protein.…”
Section: Introductionmentioning
confidence: 99%
“…They have been split in two groups, class I and class II, based on structural differences and properties of the aggregates they form [9]. Class I HFBs form highly insoluble aggregates that have the appearance of distinct rodlets and, similarly to amyloid fibrils, are characterized by cross β-structure [10]. These assemblies show outstanding stability and can be depolymerized in 100% trifluoroacetic acid (TFA) whereas class II HFBs form less stable polymers that are soluble in some organic solvents or SDS aqueous solution, and lack the rodlet appearance of class I HFBs [11].…”
Section: Introductionmentioning
confidence: 99%
“…We report that flexible regions of proteins can play a major role in the avoidance of self-assembly and aggregation. In solution EAS remains monomeric but on contact with a hydrophobichydrophilic boundary, such as an air-water interface, EAS rapidly assembles into amyloid fibrils (24) that play a functional role in the fungal life cycle (23). In the organism, however, EAS selfassembly must be tightly controlled and restricted to specific conditions and appropriate locations.…”
mentioning
confidence: 99%